Action of secretin on pancreatic enzyme secretion in man. Studies on pure pancreatic juice. Issue 8 (August 1984) - Gullo, L; Priori, P; Costa, P L; Mattioli, G; Labò, G
Abstract : The action of pure, natural secretin on the pancreatic secretion of enzymes was investigated in six patients with external transduodenal drainage of the main pancreatic duct performed after biliary tract surgery. Secretin infused for five successive 50 minute periods at increasing doses of 0.03, 0.1, 0.3, 0.9 and 2.7 clinical units (CU)/kg/h, produce a dose dependent increase in protein and lipase output. A weak but significant (p less than 0.02) increase of enzyme output above the fasting level was already observed with the lowest dose. The maximal output of protein and lipase, observed with the highest dose of secretin infused, corresponded to about 50% of that induced by maximal doses of cerulein (100 ng/kg/h) plus secretin (1 CU/kg/h). As far as bicarbonate is concerned, the lowest dose of secretin (0.03 CU/kg/h) significantly (p less than 0.001) stimulated bicarbonate output. The dose of 0.9 CU/kg/h of secretin evoked a bicarbonate output of 526 +/- 49 micromol/min; trebling the dose of secretin did not significantly increase the output of bicarbonate above this value. Increasing doses of secretin induced a dose related increase in calcium output. There was a close parallel between calcium and protein outputs, suggesting that the increase in calcium output reflected primarily an increase in the enzyme-associated fraction of pancreatic juice calcium. It is concluded that secretin stimulates pancreatic enzyme secretion in man probably by a direct action on the acinar cells.